Phase I and pharmacokinetic study of the vascular‐disrupting agent CKD‐516 (NOV120401) in patients with refractory solid tumors. Issue 2 (12th March 2020) - Kim, Hark Kyun; Kang, Jeong Won; Park, Young‐Whan; Kim, Jung Young; Kim, Minchae; Kim, Soo Jin; Kim, Se‐mi; Ho Ryu, Keun; Yoon, Seonghae; Kim, Yun; Cho, Joo‐Youn; Lee, Keun Seok; et al.
Abstract: We report a phase I pharmacological study of an oral formulation of CKD‐516, a vascular‐disrupting agent, in patients with refractory solid tumors. Twenty‐seven patients (16 in the dose‐escalation cohort and 11 in the expansion cohort) received a single daily dose (5‐25 mg) of CKD‐516 five days per week. Nausea (67%) and diarrhea (63%) were the most common treatment‐related adverse events. The recommended phase II dose of oral CKD‐516 was 20 mg/d (15 mg/d with a body surface area (BSA) <1.65 m 2 ). Notably, S‐516 half‐lives in patients receiving 15‐20 mg CKD‐516/d significantly differed between patients with and without splenomegaly that is suggestive of portal hypertension associated with liver cirrhosis (6.1 vs 4.6 hours, respectively). Of 11 patients without splenomegaly who completed at least one cycle of a daily CKD‐516 dose of either 15 or 20 mg, only one patient (9.1%) suffered from any dose‐limiting toxicity. We conclude that a daily oral dose of 15 or 20 mg CKD‐516 five days per week could be tolerable in patients without liver cirrhosis.